Six sigma distribution modeling - Sleeper Andrew D (New York McGraw-Hill, 2007)
Sleeper provides six sigma practitioners with the tools which will allow them to stand out from your competitors by using advanced statistical and modeling tools for more in-depth analysis.Understanding and properly utilizing statistical data distributio
Keywords: Applied statistics; Data processing; Distribution(Probability theory); Production control; Statistical methods; System analysis